Reckless [compact disc, unabridged] - Funke, Cornelia, 1958- (Funke, Cornelia, 1958- Reckless (Series)., 2010)
Jacob and Will Reckless have looked out for each other ever since their father disappeared, but when Jacob discovers a magical mirror that transports him to a warring world populated by witches, giants, and ogres, he keeps it to himself until Will follows him one day, with dire consequences.